Stretch‐Safe: Magnetic Connectors for Modular Stretchable Electronics. (19th August 2020) - Kettlgruber, Gerald; Danninger, Doris; Moser, Richard; Drack, Michael; Siket, Christian M.; Wirthl, Daniela; Hartmann, Florian; Mao, Guoyong; Kaltenbrunner, Martin; Bauer, Siegfried
Abstract : Stretchable Electronics The image, provided by Martin Kaltenbrunner and co‐workers (article number 2000065 ), shows magnetic interfaces serving not only as mechanical but also as electrical connectors in stretchable electronics. These connectors are safeguarded by a controlled release mechanism, preventing failure in every‐day operation and allow a modular and user‐friendly approach to the assembly of mHealth devices.